Investigating the Effectiveness of Neural Approach in Computer Assisted Translation (CAT) Systems - Ajide, Awwal Olawole (Eastern Mediterranean University, 2023)
The usefulness of neural techniques in computer-assisted translation (CAT) is thoroughly examined. The development of neural networks has significantly improved machine translation and other aspects of natural language processing (NLP). By using computer aid, CAT is an NLP task that seeks to increase the effectiveness and caliber of human translation. However, because standard statistical-based approaches lack semantic comprehension, CAT's usefulness has been constrained. With their capacity to recognize intricate linguistic structures, neural networks have demonstrated significant promise in overcoming this restriction. Comparison research between neural and conventional statistical-based methods was done to ascertain the effectiveness of neural approaches in CAT. Two datasets were employed in the investigation, one with technical and scientific documents and the other with legal words. The outcomes demonstrated that in terms of accuracy, fluency, and overall translation quality, neural-based models beat the conventional statisticalbased methods. The neural models were very good at translating colloquial language and handling complicated sentence patterns. The study also examined how many variables, including corpus size, language pairs, and training methods, affected the effectiveness of neural-based models. The results showed that the performance of neural-based models can be greatly enhanced by using larger corpus sizes and properly chosen training approaches. The results of this work show the potential of neural approaches in enhancing computer-assisted translation efficacy and emphasize the significance of taking numerous elements into account when creating and training neural-based CAT systems. Keywords: neural machine translation, computer-assisted translation, CAT system, out-of-vocabulary words, rare words, translation effectiveness, machine learning, natural language processing, deep learning, neural networks, language modeling.

Bilgisayar destekli çeviride (CAT) nöral tekniklerin kullanışlılığı bu bölümde kapsamlı bir şekilde incelenmektedir. Sinir ağlarının gelişimi, makine çevirisini ve doğal dil işlemenin (NLP) diğer yönlerini önemli ölçüde iyileştirmiştir. CAT, bilgisayar yardımı kullanarak insan çevirisinin etkinliğini ve kalitesini artırmayı amaçlayan bir NLP görevidir. Bununla birlikte, standart istatistiksel tabanlı yaklaşımlar semantik kavrayışa sahip olmadığından, CAT'in kullanışlılığı kısıtlanmıştır. Karmaşık dil yapılarını tanıma kapasiteleri ile sinir ağları, bu kısıtlamanın üstesinden gelmede önemli bir umut vaat ediyor. CAT'ta nöral yaklaşımların etkinliğini belirlemek için nöral ve geleneksel istatistiksel tabanlı yöntemler arasında bir karşılaştırma araştırması yapıldı. Soruşturmada biri teknik ve bilimsel belgeler, diğeri hukuki sözcükler içeren iki veri seti kullanıldı. Sonuçlar, doğruluk, akıcılık ve genel çeviri kalitesi açısından nöral tabanlı modellerin geleneksel istatistiksel tabanlı yöntemleri yendiğini gösterdi. Nöral modeller günlük konuşma dilini çevirmede ve karmaşık cümle kalıplarını işlemede çok iyiydi. Çalışma ayrıca, korpus boyutu, dil çiftleri ve eğitim yöntemleri dahil olmak üzere kaç değişkenin nöral tabanlı modellerin etkinliğini etkilediğini inceledi. Sonuçlar, nöral tabanlı modellerin performansının, daha büyük korpus boyutları ve uygun şekilde seçilmiş eğitim yaklaşımları kullanılarak büyük ölçüde artırılabileceğini gösterdi. Bu çalışmanın sonuçları, bilgisayar destekli çeviri etkinliğini artırmada nöral yaklaşımların potansiyelini gösteriyor ve nöral tabanlı CAT sistemleri oluştururken ve eğitirken çok sayıda unsuru dikkate almanın önemini vurguluyor. Anahtar Kelimeler: sinirsel makine çevirisi, bilgisayar destekli çeviri, CAT sistemi, kelime dağarcığı dışındaki sözcükler, nadir sözcükler, çeviri etkinliği, makine öğrenimi, doğal dil işleme, derin öğrenme, sinir ağları, dil modelleme.
Master of Technology in Information Technology. Institute of Graduate Studies and Research. Thesis (M.Tech.) - Eastern Mediterranean University, School of Computing and Technology, 2023. Supervisor: Asst. Prof. Dr. Mustafa Tanel Babagil
Keywords: Thesis Tez; School of Computing and Technology; Translators; Logic; Symbolic and mathematical; Mathematical Logic and Formal Languages; Language and languages--Computer-assisted instruction; Neural machine translation; computer-assisted translation; CAT system; out-of-vocabulary words; rare words; translation effectiveness; machine learning; natural language processing; deep learning; neural networks; language modeling.